Multilingual composing on facebook: Defining the “Social” in social constructivism and social media - Hynes, Kathleen (Journal of Interdisciplinary Studies in Education, 2019)
Social constructivist theories underpinned nearly all of the seven empiricalstudies conducted on post-secondary English Language Learners’ (ELLs’)Facebook use. However, a potentially complicated relationship exists betweenthe term “social” as education theorists conceive it and the adjective “social”used to describe online networking. Analysis shows that the former emergesfrom a paradigm that sees people’s interactions as capable of integration, whilethe latter refers to activities that tend to promote fragmentation. This suggeststhat transforming social media into a space for learning partly hinges on theinstructor’s ability to design assignments that demand greater collaboration thanFacebook asks of its users. Rather than abandoning SNSs, working within theirlimitations might create new opportunities for student engagement and learning.